Examining SLP student perceptions of reflective practice. How do students compare on the reflective practice questionnaire? - Cook, Kate; Messick, Cheryl; McAuliffe, Megan (International Journal of Practice-based Learning in Health and Social Care, 2024)
Reflective practice (RP) activities are regularly employed as part of clinical education programs for SLP. Studies examining SLP student perception of RP, suggest that in general RP activities are valued and learning occurs (Dunne et al., 2019; Tillard et al., 2018). However, it is not known whether perceptions of RP activities change as clinical placement experience increases. The impact of RP activities on outcomes such as: confidence; communication; job satisfaction; stress; uncertainty; and desire for improvement also has not been examined. Aims: 1. To determine perceptions of reflective capacity and outcomes of engaging in RP in three groups of SLP students (following their second, fourth or sixth clinical placement experience) utilizing a validated and reliable instrument. 2. To examine patterns of perceptions of reflective capacity and outcomes of engaging in RP across SLP students utilizing Hierarchical clustering (Manhattan distance). 70 SLP students completed The Reflective Practice Questionnaire (RPQ) (Priddis & Rogers, 2018; Rogers et al., 2019). The majority of SLP students perceived they had high levels of reflective capacity. In general, as SLP student clinical placement experience increased so did perception of RP abilities and subscales associated with outcomes of engaging in RP. A significant positive effect for three subscales of the RPQ (communication confidence, confidence general and job satisfaction) was found as clinical placement experience increased. Three groupings were identified as a result of Hierarchical clustering. This study provides quantitative data to support the teaching and use of RP activities with students across clinical programs.